Cx43 mediates changes in myofibroblast contraction and collagen release in human amniotic membrane defects after trauma - Costa, Eleni (2021)
The wound healing capacity of the fetal membranes after spontaneous or iatrogenic membrane rupture is unclear. We examined the healing mechanisms in amniotic membrane (AM) defects after trauma. Traumatised human AM defects were cultured for 4 days. Markers for nuclear (DAPI), cell type (vimentin, αSMA) and healing (Cx43, TGFβ1, collagen) were examined by immunofluorescence (IMF) confocal microscopy, Second Harmonic Generation (SHG) imaging and RT-qPCR. After trauma, AMCs and myofibroblasts migrated to the AM wound edge. Within four days, αSMA expressing myofibroblasts showed abundant Cx43 localized in the cytoplasmic processes. The highly contractile spindle-shaped myofibroblasts were present in the defect site and released collagen. In contrast, AMCs expressed vimentin and formed Cx43 plaques between cells found in the outer edges of the wound. Whilst AMCs were absent in the defect site, αSMA expressing myofibroblasts continued to elongate and polarize the collagen fibres. Both TGFβ1 and Cx43 gene expression were significantly increased after trauma. Cx43 has differential effects on AM cell populations that increase cellularity, contraction and potentially migration to the wound edge resulting in collagen polarisation in the AM defect site. Establishing how Cx43 regulates AM cell function could be an approach to repair defects in the membranes after trauma.